Impact of Work from Home Policy Implementation on Work Effectiveness and Productivity in Tangerang City - Indra Gunawan; Agus Kusnawan; Eso Hernawan (Fakultas Bisnis, 2021)
This research was conducted based on the desire of the researchers to find out how much influence the Work from Home policy has on the effectiveness and productivity of work, especially for workers in the Tangerang area The dependent factor studied was the Work from Home policy as the independent variable (Y), while the independent factors were effectiveness (X1) and work productivity (X2). The resulting t value for the work effectiveness variable is 0.647 with sig 0.519. The results of this significance analysis are greater than 0.05, so it means that individually the work effectiveness variable does not have an impact due to the WFH policy. The resulting t value for work productivity variable is 6.103 with sig 0.000. The results of this significant analysis are smaller than 0.05, meaning that individually the work productivity variable has a significant impact on the implementation of WFH policies. The results obtained in this study are based on the SPSS calculation, the F count is 19.504 with F sig. 0,000 where F sig. 0.000 is smaller than 0.05, so Ho is rejected. It can be interpreted that simultaneously work effectiveness (X1) and work productivity (X2) have a significant impact on the implementation of WFH policy (Y). This calculation also forms the equation Y = 9,112 + 0.108 X1 + 0.681 X2 + e. The R square value obtained from the SPSS calculation of 0.236 (23.6%) can be interpreted that work effectiveness (X1) and work productivity (X2) explain the impact of variations in the variable implementation of WFH policy (Y) by 23.6% and the rest is influenced other independent variables amounted to 76.4%.